2017
DOI: 10.1002/cne.24156
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐life environmental enrichment increases synaptic density in CA1 in a mouse model of Aβ‐associated pathology and positively influences synaptic and cognitive health in healthy ageing

Abstract: Early-life cognitive enrichment may reduce the risk of experiencing cognitive deterioration and dementia in later-life. However, an intervention to prevent or delay dementia is likely to be taken up in mid to later-life. Hence, we investigated the effects of environmental enrichment in wildtype mice and in a mouse model of Aβ neuropathology (APP /PS1 ) from 6 months of age. After 6 months of housing in standard laboratory cages, APP /PS1 (n = 27) and healthy wildtype (n = 21) mice were randomly assigned to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 79 publications
(87 reference statements)
1
21
0
Order By: Relevance
“…However, synaptic proteins SYP and PSD‐95 are increased in the hippocampus of GR+EE mice relative to those of GR+SE mice. Similarly, previous studies on AD transgenic mice or wild‐type mice also showed an improving effect of EE on hippocampal expression of genes/proteins related to synaptic plasticity. Together, these results suggest that the spatial cognition reserved by EE is associated with increased experience‐dependent synaptogenesis in young APP/PS1 mice prior to the amyloidosis onset.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, synaptic proteins SYP and PSD‐95 are increased in the hippocampus of GR+EE mice relative to those of GR+SE mice. Similarly, previous studies on AD transgenic mice or wild‐type mice also showed an improving effect of EE on hippocampal expression of genes/proteins related to synaptic plasticity. Together, these results suggest that the spatial cognition reserved by EE is associated with increased experience‐dependent synaptogenesis in young APP/PS1 mice prior to the amyloidosis onset.…”
Section: Discussionsupporting
confidence: 64%
“…We demonstrated that 8 weeks of exposure to EE improves spatial learning and memory of young APP/PS1 mice housed in a standard environment. In line with this, previous studies have revealed that enrichment has a beneficial effect on cognitive function of various AD mouse models, such as APPswe transgenic mice, APP23 transgenic mice, Tg2576 mice, APPswe/PS1dE9 mice, and PS1/PDAPP mice . However, effects of EE on the levels of Aβ in AD transgenic mice are controversial, showing three different results: decreases, increases, and no changes …”
Section: Discussionmentioning
confidence: 80%
“…Environmental enrichment (EE) has been suggested as an efficient strategy to treat human AD and AD-like animal models (12,13). EE has potential to ameliorate deficits resulting from the administration of Aβ protein oligomers (14,15). However, EE as used in animal research usually includes other variables than perception and memorization, which make it difficult to determine the nature of its eventually favorable effects.…”
mentioning
confidence: 99%
“…In animal studies, brain BDNF is increased in the hippocampus and cerebral cortex following exercise [88], as well as following environmental enrichment which also promotes physical activity (e.g., [89][90][91]). Blocking BDNF action inhibits the exercise-mediated increase in synaptic proteins [92].…”
Section: Physical Activity Bdnf and Risk Of Cognitive Declinementioning
confidence: 99%